Investigation of the relationship between adoption of minimalist and sustainable lifestyle, and individuals’ views on artificial meat - Tunçay, Güzin Yasemin; Çobanoğlu, Nesrin (Frontiers in Nutrition, 2025)
BackgroundIt is thought that due to fact that the world population is increasing and that the prediction that the world’s resources will be inadequate, the need for sustainable lifestyles, sustainable consumption, sustainable nutrition and therefore alternative food solutions such as artificial meat as a sustainable protein source will increase. In sustainable nutrition, individuals consume only what they need; in other words, they have a healthy and balanced diet. Artificial meat is also considered a form of nutrition that is environmentally sustainable, because its negative environmental effects are minimal, and it ensures food safety. The Minimalist Lifestyle, where simple living and consumption only for needs are at the forefront, is also closely related to environmental sustainability goals. A minimalist lifestyle can be considered as a form of sustainable lifestyle. Therefore, it is thought that sustainable nutrition, the minimalist lifestyle, and the consumption of artificial meat have the potential to support environmental sustainability, and that there is a significant relationship between these three themes.MethodsIn this study, the possible relationship between individuals adopting a minimalist and sustainable lifestyle, and their views on artificial meat were investigated. Two scales were used in the study. One of them is the Scale for Determining the Minimalist Lifestyle from the Point of Environmental Bioethics, and the other one is the Scale for Behaviors towards Sustainable Nutrition. In addition to these scales, the participants were asked open-ended questions about artificial meat. It was also investigated whether individuals’ minimalist tendencies positively affected their perspectives on artificial meat with survey and analysis methods.ResultsIn this study, it was determined that the majority of people who embrace minimalist lifestyle also embrace a sustainable diet. It was investigated that 65% of the participants did not have knowledge about artificial meat and 83.4% did not have knowledge about the production process. Regarding consumption preferences, 87.6% indicated that they would not choose to consume artificial meat, and approximately half of the participants (51.6%) either did not or would not hold a positive opinion about it. Furthermore, it was found that the preference for artificial meat consumption is lower among participants embracing a minimalist lifestyle. Participants have doubts about the health effects of artificial meat consumption. These results may be influenced by the cultural and religious beliefs of Turkish society.ConclusionThe research results indicate that some cultures may have a negative view of artificial meat. It is believed that awareness of the potential beneficial effects of artificial meat on the ecosystem could gradually change this perspective over time. Due to the growing world population and decreasing global resources, it is expected the need for alternative and sustainable protein sources will increase in future years. In this context, the issue of artificial meat is expected to become increasingly prominent. Various bioethical issues and dilemmas are predicted to arise. Therefore, further research should be conducted on this topic.